2019
DOI: 10.1002/bjs.11071
|View full text |Cite
|
Sign up to set email alerts
|

Time to calcitonin normalization after surgery for node-negative and node-positive medullary thyroid cancer

Abstract: Background: It remains unclear when postoperative serum calcitonin levels should be measured in patients with medullary thyroid cancer (MTC) and, specifically, whether this decision should be based on the preoperative calcitonin level or nodal status. Methods:A cohort of patients with previously untreated MTC was studied. Kaplan-Meier analyses, stratified by preoperative calcitonin level, nodal status and number of nodal metastases, were performed to determine time to calcitonin normalization after initial sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 28 publications
2
13
0
2
Order By: Relevance
“…Calcitonin normalizes in a consistent pattern in node-negative patients with preoperative calcitonin levels <1000 pg/mL (3.5–6.6 days). 17 However, patients with node-positive disease with a preoperative serum calcitonin level >1000 pg/mL took on average 57.7 days to normalize compared to 6.6 days in those without nodal metastases. Length of time to calcitonin normalization was proportional to nodal burden of disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcitonin normalizes in a consistent pattern in node-negative patients with preoperative calcitonin levels <1000 pg/mL (3.5–6.6 days). 17 However, patients with node-positive disease with a preoperative serum calcitonin level >1000 pg/mL took on average 57.7 days to normalize compared to 6.6 days in those without nodal metastases. Length of time to calcitonin normalization was proportional to nodal burden of disease.…”
Section: Resultsmentioning
confidence: 99%
“…Those with more than 10 positive nodes demonstrated a mean time to calcitonin normalization of 57.1 days compared to 5.2 days in patients with 1–5 positive nodes and 7 days in patients with 6–10 positive nodes. 17 Thus, patients with calcitonin >1000 pg/mL and those with >10 positive lymph nodes have prolonged time to calcitonin normalization which must be considered when planning timing of first post-operative calcitonin level.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that postoperative normalization of tumor marker Ctn takes time depending on the stage. Machens et al showed that this occurred at least one week postoperatively in MTC with LNM and preoperative Ctn level below 500 pg/ml, at least 14 days postoperatively in MTC with LNM and preoperative Ctn between 500.1-1000 pg/ml, and at a later time point in MTC with > 10 LNM and MTC with LNM and preoperative Ctn > 1000 pg/ml ( 6 ).…”
Section: Postoperative Follow-upmentioning
confidence: 99%
“…Current evidence suggests that the greater the number of node metastases from MTC, the higher the risk of distant metastases, and the lower the chance of biochemical cure and survival. The larger the number of node metastases removed, the longer the time to calcitonin normalization. Usually biochemical cure cannot be achieved when more than ten nodes are involved.…”
Section: Introductionmentioning
confidence: 99%